This just in : what I couldn$1 (Bt tell you on TV /s - Schieffer, Bob. (New York : G.P. Putnam$1 (Bs Sons,s, 2003)
It has been a remarkable career for Bob Schieffer, the chief Washington correspondent for CBS News. He is trusted by countless Americans to cover the stories that matter. During his extraordinary career, he has won six Emmys. In 2002 the National Press Foundation hailed him as the Broadcaster of the Year. Now the highly respected veteran newsman shares the stories he's long kept under wraps in a book The Washington Post says "is everything a memoir should be--candid, funny, and loaded with great stories about famous people ..." Schieffer goes beyond the news everyone is familiar with to share the compelling anecdotes only his colleagues were previously privy to. Says the author, "I want to tell you about the parts that didn't get on television or in the paper ..." The result is an eye-opening glimpse behind the scenes of the news business. Whether the topic is the Nixon White House or Vietnam, the JFK assassination or the 1968 election, Schieffer has a story to tell that you simply have not heard before--but are almost certain to find fascinating. Schieffer reads his own work here, delivering a pitch-perfect narration that captures every nuance of his witty and wise insights
Includes index.
Keywords: Schieffer, Bob; Journalists -- United States -- Biography